Determinan Kesiapan Berwirausaha Siswa SMK: Peran Pengetahuan Kewirausahaan, Dukungan Sosial, dan Efikasi Diri - Ramadhanti, Regita Ari; Gumilar, Rendra; Srigustini, Astri (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2026)
This study was motivated by the low level of entrepreneurial readiness among vocational high school students, even though the competency standards for vocational high school graduates are designed to prepare them for employment and entrepreneurship. The objective of this study is to determine the influence of entrepreneurial knowledge, social support, and self-efficacy on students’ entrepreneurial readiness. The research approach is quantitative using a survey method. The population of this study consists of 634 eleventh-grade students at SMK Negeri 1 Ciamis for the academic year 2025/2026. The sampling technique used is proportionate stratified random sampling, with a sample size of 245 students. The results of the study indicate that: 1) Entrepreneurial knowledge has a positive and significant effect on students’ entrepreneurial readiness. 2) Social support has a positive and significant effect on students’ entrepreneurial readiness. 3) Self-efficacy has a positive and significant effect on students’ entrepreneurial readiness. 4) Entrepreneurial knowledge, social support, and self-efficacy have a positive and significant influence on students’ entrepreneurial readiness. It can be concluded that students’ entrepreneurial readiness is shaped by the integration of cognitive aspects,the social environment, and internal beliefs that mutually influence one another in solidifying students’ career choices to become entrepreneurs.